(untitled) (Journal of Business, Universidad del Pacífico (Lima, Peru), 2026)
This article critically analyzes the extent to which the structural characteristics of the International Financial Reporting Standards for Sustainability –IFRS S1 and IFRS S2– erode the financial comparability defined in the IASB Conceptual Framework, with particular attention to paragraphs 2.24 through 2.32, which establish comparability and verifiability as enhancing qualitative characteristics indispensable to the usefulness of information. To this end, a qualitative, explanatory, and analytical-critical approach was adopted, grounded in the critical documentary analysis of primary normative sources and specialized academic literature; the analytical procedure combines the systematic identification of normative tensions, abductive reasoning, and evaluation across three comparability dimensions. The findings reveal that comparability between entities is undermined by the use of probabilistic metrics and heterogeneous reference frameworks; comparability over time is compromised by the absence of standard precision in the definition of short-, medium-, and long-term horizons; and comparability of informational content is severely affected by methodological discretion in emissions measurement and the transitional relief granted for Scope 3 emissions. The IASB Conceptual Framework, adopted by reference by the ISSB in the absence of its own conceptual framework, lacks the instruments necessary to resolve these structural tensions. As a contribution, the article proposes an integrated theoretical framework that articulates the IASB Conceptual Framework, the decision-usefulness theory of information, and critical accounting. This framework is complemented by a comparability vulnerability assessment instrument applicable by auditors and preparers in emerging adoption contexts.